Intravenous Thrombolysis in Posterior Circulation Stroke - Dorňák, Tomáš; Král, Michal; Šaňák, Daniel; Kaňovský, Petr (Frontiers in Neurology, 2019)
BACKGROUND: Intravenous thrombolysis (IVT) is a standard treatment for both anterior circulation ischemic stroke (ACIS) and posterior circulation ischemic stroke (PCIS). PCIS is a clinical syndrome associated with ischemia-related changes in the territory of the posterior circulation arteries. Embolism is the most common stroke mechanism in posterior circulation. PCIS represents 12-19% of all IVT-treated strokes. METHODS AND RESULTS: We searched the PubMed database for assessments of intracerebral hemorrhage (ICH) and clinical outcome in PCIS patients treated with IVT. ICH occurs in 0% to 6.9% of posterior ischemic stroke depending on the definition of symptomatic ICH, and any ICH in 17% to 23.4% of posterior ischemic stroke. For patients with PCIS, 38% to 49% have a favorable outcome (mRS 0-1) after IVT. Better clinical outcomes occur more often in patients with PCIS than in those with ACIS. The mortality rate among PCIS patients treated with IVT ranges from 9% to 19%; it does not differ significantly between PCIS and ACIS. CONCLUSIONS: Up to date, no data about PCIS and IVT are available from RTCs. Based on limited results from retrospective clinical studies and case series, IVT is safer for use in PCIS than in ACIS. Patients with brainstem ischemia, vertebral artery occlusion, and absence of basilar or posterior cerebral artery occlusion could be considered for treatment with IVT even in borderline cases. Time to IVT in PCIS seems to be a less crucial factor than in ACIS. IVT for PCIS may be beneficial even after 4.5 hours from symptom onset.